Transformasi Nilai dan Jati Diri Masyarakat Melayu Riau dalam Pantun di Era Modern - Arbi, Arbi; Tumangger, Agnes Sakinah; Rahmawati, Aulia Oktria; Azzahra, Fita; Sari, Gesty Puspita; Nurhusnaina, Intan (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Pantun, a traditional form of Malay poetry, serves not only as an aesthetic expression but also as a medium for transmitting cultural values and identity. In the face of modernization and globalization, pantun encounters significant challenges in maintaining its cultural relevance. This study explores the transformation of values and cultural identity of the Riau Malay community as reflected in pantun, emphasizing its role in preserving heritage in the modern era. A qualitative approach with library research was employed, utilizing classical and contemporary pantun texts as data sources. Hermeneutic analysis was applied to interpret the symbolic meanings and cultural values embedded in the pantun. The findings reveal that pantun encapsulates essential values such as politeness, respect, mutual cooperation, spirituality, and filial piety. These values contribute significantly to character development and the reinforcement of Malay cultural identity. Hence, preserving pantun is not only vital for safeguarding literary heritage but also as a cultural strategy to sustain national values and foster cultural consciousness amid the tides of modernity.